Online Patient Ratings Are Not Correlated with Total Knee Replacement Surgeon–Specific Outcomes. Issue 2 (July 2018) - Trehan, Samir K.; Nguyen, Joseph T.; Marx, Robert; Cross, Michael B.; Pan, Ting J.; Daluiski, Aaron; Lyman, Stephen
Background: Despite potential concerns regarding their validity, physician-rating websites continue to grow in number and utilization and feature prominently on major search engines, potentially affecting patient decision-making regarding physician selection. Questions/Purposes: We sought to determine whether patient ratings on public physician-rating websites correlate with surgeon-specific outcomes for high-volume total knee replacement (TKR) surgeons in New York State (NYS) from 2010 to 2012. Methods: Online patient ratings were compared to surgeon-specific outcomes from the Statewide Planning and Research Cooperative System (SPARCS) database from the NYS Department of Health. For each surgeon, we determined the infection rate, re-admission rate, and revision surgery rate within the study period, as well as the mean inpatient length of stay, for TKR from the SPARCS database. Online ratings were collected from two physician-rating websites (Vitals.com andHealthGrades.com ). Results: One hundred seventy-four high-volume TKR surgeons were identified in NYS from 2010 to 2012. The mean rates of in-hospital infection, 90-day infection, 30-day re-admission, 90-day re-admission, and revision surgery were 0.25, 1.00, 4.89, 8.43, and 1.31%, respectively. The mean number of ratings for individual surgeons onHealthGrades.com andVitals.com were 24.0 (range: 0 to 109) and 19.3 (range: 0 to 114), respectively, and mean overall ratings were 4.2 and 4.1 (out of 5) stars, respectively. As with online patient ratings of individual surgeons, variability was observed in the total adverse event rate distribution for individual surgeons. Despite sufficient variability in both online patient rating and surgeon-specific outcomes for high-volume TKR surgeons in NYS, no correlation was observed. Conclusion: There was no correlation between surgeon-specific TKR outcome measures and online patient ratings. We therefore advise that patients exert caution when interpreting ratings on these websites.